Acid Rock Drainage on slopes from Route 27 San José - Caldera, Costa Rica - Ruiz, Paulo (2015)
This study focuses on determinate the presence of acid rock drainage (ARD) on two slopes on Route27, Costa Rica, by analysis of paste pH and geochemistry of superficial water. The laboratory results (samples with pH up to 1,5), and the physical evidence observed in the field, shows that in fact there is ARD in some slopes. The ARD on the route is directly affecting the chemical and physical properties of the shotcrete on the slopes, welded steel and ditch for the surface water management, causing its collapse and creating a hazard for users. The importance of identify this chemical and physical process that is weathering the materials of the slopes in the road cuts, it’s essential for the right corrective action and resolve the problem or at least minimize the negative effects and their influence on slope instability of the route.